COMPORTAMENTO DIURNO DE BOVINOS DE CORTE EM PASTEJO RECEBENDO SUPLEMENTO CONTENDO 25-OH VITAMINA D3 - Prado Moraes , Luana; Perdigão , Alexandre; Chaves Devechio , Gracielle; Chaves Devechio , Gracielle; Conrado Cerutti , Thays; Miguel da Silva Junior , Jarbas; Jorge Fernandes , Henrique (ANAIS DO ENIC, 2026)
-